Inhibin B and the ovarian follicular reserve - Nahás, Eliana Aguiar Petri [UNESP]; Pontes, Anaglória [UNESP] (My University, 2002)
Inhibins are dimeric glycoproteins composed of an α-subunit and a βA-subunit (inhibin A) or βB-subunit (inhibin B), which inhibits pituitary gonadotropin secretion of FSH. The inhibin B is a product of the cohort of antral follicles. The ovarian follicle number decrease steadily as a function of increasing age, with consequent falls in the levels of inhibin B and increase of FSH levels. It is sufficient to maintain ovulatory function and continued secretion of estradiol. Elevated FSH levels seem to occur late in the sequence of events associated with ovarian failure. The inhibin B, produced by granulosa cells, is the earliest marker of the decline in ovarian follicular reserve across reproductive aging.
Keywords: Inhibin B; Ovarian reserve; biological marker; estradiol; follitropin; glycoprotein; gonadotropin; inhibin A; inhibin B; protein subunit; adult; age; aging; alpha chain; cell secretion; controlled study; female; follitropin blood level; genital system; gonadotropin release; granulosa cell; human; inhibition kinetics; ovary follicle; ovary insufficiency; ovulation